Opinion Mining of Light Rail Transit Development in Indonesia - Sarifah Putri Raflesia; Dinda Lestarini; Firdaus Firdaus; Desty Rodiah (Institute of Advanced Engineering and Science, 2018)
Light rail transit (LRT), or fast tram is urban public transport using rolling stock similar to a tramway, but operating at a higher capacity, and often on an exclusive right-of-way. Indonesia as one of developing countries has been developed the LRT in two cities of Indonesia, Palembang and Jakarta. There are opinions toward the development of LRT, negative and positive opinions. To reveal the level of LRT development acceptance, this research uses machine learning approach to analyze the data which is gathered through social media. By conducting this paper, the data is modeled and classified in order to analyze the social sentiment towards the LRT development.